Glycated human albumin alters mitochondrial respiration in preadipocyte 3T3‐L1 cells. (22nd May 2017) - Baret, Pascal; Le Sage, Fanny; Planesse, Cynthia; Meilhac, Olivier; Devin, Anne; Bourdon, Emmanuel; Rondeau, Philippe
Abstract: Diabetes and obesity are strongly associated with increased levels of circulating advanced glycation end products (AGEs) and reactive oxygen species (ROS). These two molecular phenomena affect the physiology of adipose tissue, a biological driver of the metabolic syndrome, leading to an inflammatory profile and insulin resistance, which could contribute to obesity/diabetes‐associated complications, such as cardiovascular diseases. Herein, we investigated the impact of AGEs on mitochondrial bioenergetics in murine preadipocyte cells (3T3‐L1) and cellular redox homeostasis. We show that incubation of preadipocytes with AGEs stimulates mitochondrial activity and respiration while inducing oxidative stress. This AGE‐induced intracellular ROS production was blocked by diphenylene iodonium, an NAD(P)H oxidase inhibitor. In parallel, antioxidant enzymes (catalase, superoxide dismutase, and glutathione peroxidase) were found to be activated upon AGE treatment. Our results suggest that AGE‐induced oxidative stress is generated by NAD(P)H oxidase and leads to a cellular proliferation arrest associated with enhanced mitochondrial metabolism and biogenesis, and with increased levels of ROS‐detoxifying enzymes, as well. These new data show how AGEs may be involved in hyperglycemia‐induced oxidative damage in preadipocytes and their potential links to diabetes progression. © 2017 BioFactors, 43(4):577–592, 2017